2000
DOI: 10.1108/01443570010304288
|View full text |Cite
|
Sign up to set email alerts
|

Management practices for environmental innovation and performance

Abstract: This paper explores whether there are discernible differences in the environmental innovation and performance of US chemical firms that can be explained by differences in the management practices and characteristics of the firms. Using data from a national survey, firm visits, and phone interviews, this research assesses the pervasiveness of the adoption of environmental management practices. It also assesses whether the adoption of these practices is related to leadership in environmental innovation and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
175
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(199 citation statements)
references
References 5 publications
11
175
1
12
Order By: Relevance
“…Likewise, other aspects of environmental management not considered in the standard or during this study may influence environmental performance. For example, employee mobilization and employee awareness and participation in the environmental actions of an organization can have a non-negligible impact on performance in this area (Boiral, 1998;Kitazawa and Sarkis, 2000;Ruiz-Quintanilla et al, 1996;Theyel, 2000). It would be interesting to evaluate the extent to which ISO 14001 certification contributes to such mobilization and examine if the efficiency or inefficiency of the standard does not depend on real employee support of this management system.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other aspects of environmental management not considered in the standard or during this study may influence environmental performance. For example, employee mobilization and employee awareness and participation in the environmental actions of an organization can have a non-negligible impact on performance in this area (Boiral, 1998;Kitazawa and Sarkis, 2000;Ruiz-Quintanilla et al, 1996;Theyel, 2000). It would be interesting to evaluate the extent to which ISO 14001 certification contributes to such mobilization and examine if the efficiency or inefficiency of the standard does not depend on real employee support of this management system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to systematically explore the relationship between GP, GI and green performance. There are no previous studies focusing on environmental yet in Malaysian automotive industry but most of the studies just only reviewed in manufacturing process (Theyel, 2000;Rusinko, 2007;Zhu, et al, 2007;Green Jr, et al, 2012). Thus, we believe by exploring the GP and GI will be benefit toward Malaysian automotive industries in order to improve their green performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, industries need to apply of GP such as green supply chain management practices, green lean six sigma, and green balanced scorecard strategy to improving their profits and performance (Theyel, 2000). According to Zhu (2010), implementation of GP such as green purchasing, customer cooperation with green consideration, eco-design and investment recovery have made improvement for green performance.…”
mentioning
confidence: 99%
“…Many studies have demonstrated the close relationship between employee initiatives and the environmental performance of organizations (Boiral 2005). For example, studies based on the Environmental Protection Agency's Toxic Release Inventory database have measured the positive relationship between employee environmental commitment and pollution reduction (Ruiz-Quintanilla et al 1996;Theyel 2000). Other studies have shown the importance of employee participation in various green initiatives (pollution prevention, waste management, environmental committees, etc.)…”
Section: The Contribution Of Employee Initiatives To Corporate Greeningmentioning
confidence: 99%
“…Employee involvement has mainly been viewed as a general requirement that is positively correlated with the success of a range of organizational greening practices (Hanna et al 2000;Andersson and Bateman 2000;Jiang and Bansal 2003;Walley and Stubbs 2000;Boiral 2007;Theyel 2000). According to Ramus and Killmer (2007), corporate greening behaviours are generally based on unrewarded and extra-role behaviours contributing both to the collective welfare and to organizational effectiveness.…”
Section: Exploring Organizational Citizenship Behaviour For the Envirmentioning
confidence: 99%